2014
DOI: 10.1152/ajpcell.00252.2014
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for carbon monoxide as a potent regulator of intracellular Ca2+ and nitric oxide in rat pancreatic acinar cells

Abstract: Carbon monoxide (CO) is known as an essential gaseous messenger that regulates a wide array of physiological and pathological processes, similar to nitric oxide (NO) and hydrogen sulfide. The aim of the present study was to elucidate the potential role of CO in Ca(2+) homeostasis and to explore the underlying mechanisms in pancreatic acinar cells. The exogenous application of a CO-releasing molecule dose-dependently increased intracellular Ca(2+) concentration ([Ca(2+)]i). A heme oxygenase (HO) inducer increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
5
17
0
Order By: Relevance
“…This effect appeared to be dependent on the CO released by CORM-2 because iCORM-2, which did not liberate CO, had no effect on the calcium levels. The time course is similar to what was previously observed in rat pancreatic acinar cells when 100 or 300 µM of CORM-2 was applied to the cells [31]. However, in pancreatic cells, the [Ca 2+ ] i changes were found to be oscillatory at medium concentrations (0.4 – 0.5 mM) in the extracellular solution, and monophasic (1 mM) at the highest concentration, which is typical of pancreatic acini cells when stimulated with physiological secretagogues such as CCK-8 or acetylcholine [31].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This effect appeared to be dependent on the CO released by CORM-2 because iCORM-2, which did not liberate CO, had no effect on the calcium levels. The time course is similar to what was previously observed in rat pancreatic acinar cells when 100 or 300 µM of CORM-2 was applied to the cells [31]. However, in pancreatic cells, the [Ca 2+ ] i changes were found to be oscillatory at medium concentrations (0.4 – 0.5 mM) in the extracellular solution, and monophasic (1 mM) at the highest concentration, which is typical of pancreatic acini cells when stimulated with physiological secretagogues such as CCK-8 or acetylcholine [31].…”
Section: Discussionsupporting
confidence: 84%
“…The time course is similar to what was previously observed in rat pancreatic acinar cells when 100 or 300 µM of CORM-2 was applied to the cells [31]. However, in pancreatic cells, the [Ca 2+ ] i changes were found to be oscillatory at medium concentrations (0.4 – 0.5 mM) in the extracellular solution, and monophasic (1 mM) at the highest concentration, which is typical of pancreatic acini cells when stimulated with physiological secretagogues such as CCK-8 or acetylcholine [31]. The fact that calcium increase induced by CORM-2 could be abolished in cells superfused with Ca 2+ -free KH solution or by pretreatment of the cells with PLC inhibitor U73122, suggests a joint participation of both intracellular calcium release and extracellular calcium entry.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In fact, it has even been suggested that carbon monoxide may possess a potential therapeutic role in AP [97]. The various mechanisms suggested for its ameliorative effect in AP include regulation of intracellular Ca þ2 and NO e thereby controlling pancreatic exocrine secretion [98], suppression of nuclear factor NF-kappa B activation [99] as well as tissue protection and anti-proliferative effects [100].…”
Section: Carbon Monoxidementioning
confidence: 99%